Terra firma-forme dermatosis: a hospital-based clinico-epidemiological study at a tertiary care centre in northern India - Ramesh Kumar; Arti Singh; Rozy Badyal; Suresh Kumar Jain; Asha Nyati (Wolters Kluwer Medknow Publications, 2020)
Background: Terra firma-forme dermatosis is an idiopathic keratinization disorder characterized by acquired, dirt-like plaques despite normal hygiene which was first described in 1987. Aims: We conducted a clinical study in patients who presented with Terra-firma forme dermatosis. In this we describe the clinical features of Terra firma-forme dermatosis along with a proposal of its diagnostic criteria. Methods: A prospective study was conducted at the dermatology department of a tertiary care hospital to identify cases of Terra firma-forme dermatosis diagnosed over a period of 14 months (July, 2016, to September, 2017). The diagnosis of Terra firma-forme dermatosis was confirmed in all patients who had complete resolution of each lesion after the application of 70% isopropyl alcohol. Results: Prevalence of Terra firma-forme dermatosis was 0.05% at our outpatient department. Male to female sex ratio was 4:1(37:9). 46 patients with Terra firma-forme dermatosis were identified, including 27 (58.6%) who presented with it as their primary concern. 36 (78.26 %) were from 6 to 18 years of age group. The mean duration of lesions was 6.86 months. The most common location was the neck. The commonest cause was ignorance regarding proper cleansing techniques, inadequate pressure while scrubbing the affected area. Limitations: A small sample size and relatively short duration of follow up. Conclusions: Terra-firma forme dermatosis is a benign dermatologic condition. Awareness among the clinicians about the existence of Terra firma-forme dermatosis is essential to save time for the clinician and to reduce the economic burden on the patient.